Thymoquinone Inhibits Virulence Related Traits of Cronobacter sakazakii ATCC 29544 and Has Anti-biofilm Formation Potential - Shi, Chao; Yan, Chunhong; Sui, Yue; Sun, Yi; Guo, Du; Chen, Yifei; Jin, Tong; Peng, Xiaoli; Ma, Linlin; Xia, Xiaodong (Frontiers in Microbiology, 2017)
The aim of this study was to determine whether thymoquinone, the principal active ingredient in the volatile oil of Nigella sativa seeds, could suppress certain virulence traits of C. sakazakii ATCC 29544 which contribute to infection. Sub-inhibitory concentrations of thymoquinone significantly decreased motility, quorum sensing, and endotoxin production of C. sakazakii ATCC 29544 and biofilm formation of C. sakazakii 7-17. Thymoquinone substantially reduced the adhesion and invasion of C. sakazakii ATCC 29544 to HT-29 cells and decreased the number of intracellular bacterial cells within the RAW 264.7 macrophage cells. Thymoquinone also repressed the transcription of sixteen genes involved in the virulence. These findings suggest that thymoquinone could attenuated virulence-related traits of C. sakazakii ATCC 29544, and its effects on other C. sakazakii strains and in vivo C. sakazakii infection need further investigation.